Bioorganic synthesis, characterization and evaluation of a natural phenolic lipid - Juliya Johny (Biotechnology Reports, 2019)
The first synthesis of a phenolic natural monoacylglycerol (1- [11-(ferulyloxy) undecanoyl)] glycerol) was carried out by bioorganic synthesis starting from ferulic acid. The synthetic route of the target lipidic compound was designed involving a chemo-enzymatic approach using immobilized Candida antarctica lipase as biocatalyst in two of the steps conducted in organic medium. The prepared lipidic compound was characterized by using spectral data and evaluated for antimicrobial, antioxidant and cytotoxic studies to examine its potential. The synthesized compound showed moderate antimicrobial activity and showed very good antioxidant activity in DPPH radical scavenging assay and also in oxidation inhibition in soybean oil by differential scanning calorimetry. The cytotoxic studies of the synthetic lipid showed promising activity against A549 and HeLa cancer cell lines with IC50 values of 9.102 and 9.886 μM respectively. The prepared compound can be useful in designing novel phenolic lipids with potential applications in cosmetic and biomedical fields. Keywords: Phenolic lipid, Monoacylglycerol, Lipase, Antioxidant, Antimicrobial, Cytotoxicity